Surgical management of an incarcerated uterus in a gynecological patient: A case report - Fatimah Z. Fahimuddin; Rebecca Murphy; Michael O'Shaughnessy (Elsevier, 2019)
Uterine incarceration is most often described as occurring in pregnancies. Presenting with severe pelvic pain, urinary retention, and in some cases spontaneous abortion, this complication often arises at 12-15 weeks of gestational age. Although usually considered an obstetrical complication, uterine incarceration can occur in nongravid females. This case report presents a gynecological patient with acute urinary retention secondary to uterine incarceration. The patient chose surgical management, and surgery provided immediate symptomatic relief. Our case highlights an uncommon etiology of acute urinary retention and demonstrates the importance of considering the diagnosis of uterine incarceration in nongravid as well as gravid females. Keywords: Incarcerated uterus, Doyen tumor screw, Multi-fibroid